2007
DOI: 10.1111/j.1551-2916.2007.02069.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anisotropic Microstructure on the Viscous Properties of an LTCC Material

Abstract: The sintering behavior of a glass–ceramic (commercial material Ceramtape GC) was characterized using the discontinuous sinter‐forging technique. The uniaxial viscosity Ep and the viscous Poisson's ratio np of the composite body were determined as a function of density. Particular attention was paid to microstructural changes in order to quantify the anisotropy induced by load application. Pores and alumina particles were found to be both oriented perpendicular to the applied load direction. Finally, the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…[11][12][13] The additional pressure increases the vacancy gradients naturally occurring during free sintering by solid state sintering, leading to increased driving force for material transport along grain boundaries, help to redistribute matter by viscous flow from regions of high local pressure to regions of low pressure or to improve particle rearrangement when a liquid phase is present. Glass based materials are very sensitive to mechanical stresses applied during sintering, as evidenced by Ollagnier et al 14 on Low Temperature Co-fired Ceramics and demonstrated in previous studies from dilatometric sintering data. 15 Stress induced anisotropy characterized by elongated pore shape and particular orientation could be observed in such materials.…”
Section: Introductionmentioning
confidence: 74%
“…[11][12][13] The additional pressure increases the vacancy gradients naturally occurring during free sintering by solid state sintering, leading to increased driving force for material transport along grain boundaries, help to redistribute matter by viscous flow from regions of high local pressure to regions of low pressure or to improve particle rearrangement when a liquid phase is present. Glass based materials are very sensitive to mechanical stresses applied during sintering, as evidenced by Ollagnier et al 14 on Low Temperature Co-fired Ceramics and demonstrated in previous studies from dilatometric sintering data. 15 Stress induced anisotropy characterized by elongated pore shape and particular orientation could be observed in such materials.…”
Section: Introductionmentioning
confidence: 74%
“…16 Numerous papers focus on sintering of GMC concerning various applicative aspects, [17][18][19][20][21][22] the effect of rigid inclusions on the effective composite viscosity, 23 sinter anisotropy, 24 sinter retardation, [25][26][27] as well as the coexistence of solid and liquid phases. [28][29][30][31][32] Recently, sinter-forging or loading dilatometry studies on LTCC were focused on the anisotropic constrained sintering characteristics and microstructure of LTCC [33][34][35][36] analyzing respective viscous properties and sintering stress. The macroscopic description of constrained sintering was based on the concept of the viscoelastic analogy 37,38 and related constitutive models.…”
Section: Introductionmentioning
confidence: 99%
“…the integrated planar or segmented in series design of Rolls-Royce Fuel Cell Systems [4], the support does not shrink significantly during sintering of the electrolyte. The constraint generates a tensile stress during sintering that can lead to crack-like defects [5], delaminations and unfavourable pore orientation [6][7][8] in the films. If the defects and pores are large enough or penetrate the electrolyte film they can lead to lowered fuel efficiency and creation of local "hot-spots" that cause mechanical damage to the cells.…”
Section: Introductionmentioning
confidence: 99%